1998
DOI: 10.1091/mbc.9.5.1065
|View full text |Cite
|
Sign up to set email alerts
|

Fission Yeast Ste9, a Homolog of Hct1/Cdh1 and Fizzy-related, Is a Novel Negative Regulator of Cell Cycle Progression during G1-Phase

Abstract: When proliferating fission yeast cells are exposed to nitrogen starvation, they initiate conjugation and differentiate into ascospores. Cell cycle arrest in the G1-phase is one of the prerequisites for cell differentiation, because conjugation occurs only in the pre-Start G1-phase. The role ofste9 + in the cell cycle progression was investigated. Ste9 is a WD-repeat protein that is highly homologous to Hct1/Cdh1 and Fizzy-related. The ste9 mutants were sterile because they were defective in cell cycle arrest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 80 publications
5
125
0
3
Order By: Relevance
“…However, we found that deletion of ste9/srw1 had little effect on the frequency of chromosomal abnormalities observed in mcs1-77 cells and by inference Cut2 stability. Because ubiquitination of Cut2 is not regulated by APC Ste9 but rather by a related complex, APC Slp1 , our results suggest that the MBF complex has an additional role in controlling APC activity (Funabiki et al, 1996;Matsumoto, 1997;Yamaguchi et al, 1997;Kitamura et al, 1998;Kominani et al, 1998). One obvious possibility is that the MBF complex may control the periodic transcription of one or more components or activators of the APC Slp1 complex.…”
Section: Ste9mentioning
confidence: 78%
See 2 more Smart Citations
“…However, we found that deletion of ste9/srw1 had little effect on the frequency of chromosomal abnormalities observed in mcs1-77 cells and by inference Cut2 stability. Because ubiquitination of Cut2 is not regulated by APC Ste9 but rather by a related complex, APC Slp1 , our results suggest that the MBF complex has an additional role in controlling APC activity (Funabiki et al, 1996;Matsumoto, 1997;Yamaguchi et al, 1997;Kitamura et al, 1998;Kominani et al, 1998). One obvious possibility is that the MBF complex may control the periodic transcription of one or more components or activators of the APC Slp1 complex.…”
Section: Ste9mentioning
confidence: 78%
“…Because APC-mediated degradation ceases after cells pass START, we suggest that repression of the MBF complex may play a key role in the inactivation of APC at this time. We considered that this may be due to either cell cycle-regulated production or modification of an APC subunit(s) or adaptor proteins such as Ste9/Srw1 (Yamaguchi et al, 1997;Kitamura et al, 1998;Kominani et al, 1998). In particular, we focused our attention on ste9/srw1, because it had been isolated previously as a multicopy suppressor of the mitotic catastrophe phenotype of ⌬mik1 wee1-50 cells at high temperature (Yamaguchi et al, 1997;H.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cdc13 degradation is directed by proteins from the APC complex, which recognize the Destruction Box (DB) present in some cyclins. Three known APC-complex proteins in S. pombe are Slp1, in mitosis, Ste9, in G1 and Mfr1/Fzr1 present during meiosis and sporulation (Asakawa et al, 2001;Blanco et al, 2001;Kitamura et al, 1998;Matsumoto, 1997;Yamada et al, 2000;Yamaguchi et al, 1997). Cdc13 main function is to promote the events of mitosis and avoid re-initiation of S phase (endoreduplication).…”
Section: Regulation Of Cdc2 By Cyclinsmentioning
confidence: 99%
“…At its core are antagonistic interactions between Cdc13͞Cdc2 (M-phase promoting factor, MPF) and its negative regulators, Ste9, Rum1, and Wee1͞Mik1. Ste9 targets Cdc13 subunits for ubiquitination by the APC (15,16). Rum1 is a cyclin-dependent kinase inhibitor, which reversibly binds to Cdc13͞Cdc2 and inhibits its activity (17).…”
Section: The Modelmentioning
confidence: 99%